Formulasi Tablet Matriks Mukoadhesif Diltiazem Hidroklorida Menggunakan Hidroksi Propil Metil Selulosa dan Carbopol 940 - Siti Sofiah; Faizatun Faizatun; Yulia Riyana (Fakultas Farmasi Universitas Pancasila, 2007)
Diltiazem hydrochloride has a half life of 3-4 hours and a bioavailability of 40%. The influence of a mixture of carbopol 940 and hydroxypropyl methyl cellulose as a mucoadhesive matrix on tablets made by the wet granulation method, had been determined by the dissolution and “wash off method. The result showed that increasing the concentration of carbopol 940 decreased the dissolution rate. The concentration of carbopol 940 and hydroxypropyl methyl cellulose in formula I (0%; 40%), II (5%; 35%), III (10%; 30%), IV (15%; 25%), and V (20%; 20%) released respectively 75,99%; 74,08%; 73,07%; 72,04%; and 71,29% diltiazem hydrochloride. The higher the concentration of carbopol 940 in acid solution, the shorter is the mucoadhesive action: 2 hours in formula I and II, and 1 hour in formula III, IV, and V. All of the formulas (pH 7,2) did not show a difference in mucoadhesive duration; after 8 hours, still attached to the mucosa of the small intestines.